Efek Hypno-Pressure Terhadap Penurunan Frekuensi Denyut Nadi pada Pasien dengan Gangguan Kardiovaskuler - Nugraha, Dwi Antara (Jurnal Indonesia Sehat, 2023)
Background: Cardiovascular disorders and increased heart rate are two variables that have a relationship with the patient's prognosis. An increase in heart rate will have a negative effect on cardiovascular. Pharmacological management with digoxin, propranolol, diltiazem, and verapamil has been carried out. Likewise non-pharmacological management using hypnotherapy and also acupressure (hypno-pressure). Objective: Analyzing changes in pre-post pulse frequency values ??in the intervention group, and in the control group. Methodology: This research is a quasy experiment with pretest-posttest with control group. The population in this study were all patients with tachycardia, experiencing cardiovascular disorders and meeting the inclusion criteria. The sample size for the intervention group was 28 respondents and the control group was 28 respondents. The sampling technique used is simple random sampling. Different test using Chi-Square and Mann Whiteney. Data normality test using Shapiro-Wilk. Bivariate analysis using Independent t-Test and Independent t-Test. Results:  Hypno-pressure 30 minutes 2 sessions has the effect of lowering the average value of pulse frequency. The strength of the effect of the independent variable on the dependent variable is strong, with an effect size value of hypno-pressure on pulse frequency of 1.86. Conclusion:  Statistically, hypno-pressure 30 minutes 2 sessions is effective in reducing pulse frequency in the first 12 hours of inpatients suffering from cardiovascular disorders.